Rethinking Infrastructure in Latin America and the Caribbean : Spending Better to Achieve More - Fay, Marianne; Andres, Luis Alberto; Fox, Charles; Narloch, Ulf; Staub, Stephane; Slawson, Michael (World Bank, Washington, DC, 2017)
Latin America and the Caribbean does not have the infrastructure it needs, or deserves, given its income. Many argue that the solution is to spend more; by contrast, this report has one main message: Latin America can dramatically narrow its infrastructure service gap by spending efficiently on the right things.